Characteristics of a national level female weightlifter peaking for competition: A case study - Bazyler, C. D.; Mizuguchi, S.; Zourdos, M. C.; Sato, K.; Kavanaugh, A. A.; DeWeese, B. H.; Breuel, K. F.; Stone, M. H. (The Journal of Strength and Conditioning Research, 2018)
This study investigated physiological and performance changes of a national-level 69 kg female weightlifter after 3 competition phases over a 28-week training period. The athlete first trained for a regional championship (weeks 1-12), followed by a local competition (weeks 13-23) and the national championship (weeks 24-28). Body mass, vastus lateralis cross-sectional area (CSA), and unloaded and loaded squat jump performance were assessed weekly during each 4-week competition phase. Serum biomarkers and dynamic midthigh pulls were assessed before and after each competition phase. Weightlifting performance goals were met for the regional championship (total = 200 kg) and the local competition (total = 193 kg), but not the national championship (total = 196 kg). She lost more body mass in preparation for Nationals (-6.0 kg) compared with regionals (-2.5 kg) and the local competition (+2.2 kg). Vastus lateralis CSA very likely decreased after Nationals (precision = 99%, effect size = 2.08). Her testosterone:cortisol ratio likely increased (88%, 2.64), whereas interleukin-6 (79%, 2.47) and tumor necrosis factor-alpha (81%, 3.59) likely decreased after Nationals. Serum myostatin (99%, 1.95) and decorin (99%, 1.96) very likely decreased after the local competition. Unloaded squat jump height likely increased the week of regionals (89%, 0.95) and the local competition (99%, 1.83), whereas unloaded and loaded squat jump height possibly (69%, 0.99) and likely (82%, 1.52) decreased the week of Nationals. Dynamic midthigh pull vertical displacement likely increased after regionals (93%, 0.84) and likely decreased after Nationals (94%, 0.87). These findings indicate that biomarkers of stress, inflammation, and hypertrophy are related to changes in training volume-load; however, performance measures are needed to assess competition preparedness. Considering the reductions in muscle CSA corresponding with the large reductions in body mass and underperformance at the national championship, sport scientists, and coaches should instruct weightlifters to not attempt large losses in body mass (e.g., >3 kg) close to competition (e.g., <1week).